2023
DOI: 10.1186/s12882-023-03255-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two ferritin assay platforms to assess their level of agreement in measuring serum and plasma ferritin levels in patients with chronic kidney disease

Abstract: Background Ferritin levels are used to make decisions on therapy of iron deficiency in patients with chronic kidney disease (CKD). Hyperferritinaemia, common among patients with CKD from the Northern Territory (NT) of Australia, makes use of ferritin levels as per clinical guidelines challenging. No gold standard assay exists for measuring ferritin levels. Significant variability between results from different assays creates challenges for clinical decision-making regarding iron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This means that it is important for the clinical management of a patient that the analyses are carried out in the same laboratory. A similar conclusion was reached by researchers studying ferritin values among patients with chronic kidney disease [29]. Indeed, in this study, 179 blood samples were analyzed for ferritin using two different assays, with an observed bias of up to 49%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This means that it is important for the clinical management of a patient that the analyses are carried out in the same laboratory. A similar conclusion was reached by researchers studying ferritin values among patients with chronic kidney disease [29]. Indeed, in this study, 179 blood samples were analyzed for ferritin using two different assays, with an observed bias of up to 49%.…”
Section: Discussionsupporting
confidence: 84%
“…The present data confirm previous studies, such as those of Birgegård in 1980, which compared samples from nine subjects, or more recently, those of Snozek et al in 2021, which compared serum and heparinized plasma, in which a correlation of 0.9992 was retrieved between these two matrices [27,28]. In their 2023 study, Majoni et al observed identical results using the chemiluminescent microparticle immunoassay (CMIA) method, but an overestimation of 5% with serum compared to heparinized plasma matrix using a two-phase immunometric method [29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation